Architectural morphology and construction techniques of traditional Yoran houses, Turkey - Yergun, U.; Gencer, C. I.; Celebioglu, B.; Ciftci, A. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2014)
Yoran, home of ancient Didyma, is a traditional Anatolian town on the Aegean coast. Here, the traditional houses were built by Greeks during the Ottoman period, which are usually one or two storeys high cubical masonry units. In this study, the construction techniques and building materials of the vernacular fabric were documented and recorded in detail with photographs, surveys and interviews with two local masonry masters and inhabitants. This paper analyses the planning principles of the masonry houses; the original function of spaces; the construction techniques and materials of foundations, walls, floors, roof coverings; as well as exterior architectural elements, such as sheds, wells, ovens and toilets. Most of the traditional buildings in Yoran were abandoned and deteriorated after 1955 earthquake. This study aims to document the houses of Yoran, in order to revitalize them and define intervention proposals for their preservation.
Keywords: Architecture; Engineering; Environmental Sciences & Ecology